Formulasi Instrumen Kebijakan Lingkungan di Kabupaten Banyuwangi - Akbar Pandu Dwinugraha (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
The purpose of this study to describe and analyze the core issues relating to the environment in Banyuwangi Regency. This research used descriptive research with a qualitative approach. Informants in this study included Development Planning Agency at Regional Level; Environment Agency; Sanitation Agency; Public Works and Regional Road Agency; Public Works Irrigation Agency; Industry, Trade and Mines Agency; Agriculture Agency; and Regional Disaster Management Agency. Data were analyzed with interactive techniques that included data collection, data reduction, data display and verification. The results showed that the main issues in environment scope in the Banyuwangi Regency including tsunamis, volcanoes and other disasters; conversion of productive land; environmental pollution (water, air and soil); garbage and urban sanitation; as well as agricultural land.